Crack formation within ceramics via coupled multiscale genome and XFEM predictions under various loading conditions. (December 2018) - Dong, Xiangyang; Shin, Yung C.
Highlights: A new coupled multiscale genome and XFEM modeling method is proposed to predict crack formation. The new method is much more computationally efficient in predicting crack formation in heterogeneous materials. The modeling is applied to SiC ceramics under various loading conditions. The validity of the new model is demonstrated with comparison with experiments. Abstract: Because of the complex heterogeneous microstructure of ceramics, predicting crack formation within ceramics is still a challenge. The extended finite element method (XFEM) serves as a good tool for fracture prediction but is incapable of considering heterogeneous microstructure. In this paper, a numerical framework is developed to model cracks within ceramics by coupling a multiscale genome model with XFEM. XFEM is embedded in the formulation of the multiscale genome through the variational asymptotic method for unit cell homogenization (VAMUCH). The implementation of both multiscale genome model and XFEM retains the capabilities of XFEM in modeling fracture while providing accurate predictions by considering heterogeneous microstructure. The crack formation within SiC ceramics under different loading conditions is simulated in comparison with experiments in order to assess the validity of the proposed method. It is shown that the developed model captures the typical characteristics of crack formation within silicon carbide (SiC) ceramics under bending and indentation loadings. The predicted cutting forces and crack depth exhibit a good agreement with the experimental results during machining processes.